A method for preparing a foamed sheet catalyst for hydrogen storage / dehydrogenation in organic liquids
By mixing the Pd or Ru compounds with the nanocarrier and binder and immersing them in the foam metal, foam sheet-like catalysts are prepared, which solves the problem of less exposure of catalyst active sites in the prior art, and achieves efficient catalytic activity and stability.
Patent Information
- Application Number
- CN202411426766.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, the number of active sites of hydrogen-added catalysts used in fixed beds is exposed, resulting in low catalytic activity.
The foam sheet-like catalyst was prepared by mixing the compound of Pd or Ru with the nanocarrier and the binder to form a suspension, and the foam metal was immersed therein, and the foam sheet-like catalyst was prepared after drying and reducing treatment.
The catalytic activity of the catalyst is improved, the exposure of active sites is increased, the cost of catalyst molding is reduced, and the catalytic stability in LOHC is improved.
Smart Images

Figure CN119733528A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and hydrogen storage, and in particular relates to a method for preparing a foam sheet catalyst for organic liquid hydrogen storage / desorption. Background Art
[0002] As the greenhouse effect caused by anthropogenic emissions becomes more and more serious, it brings about worrying climate change, environmental problems and sustainable development issues, which have promoted the development of a carbon-free energy system. To achieve this strategy, hydrogen has been proposed as an environmentally friendly energy carrier, but to develop a competitive hydrogen economy, there is still a lack of safe and efficient large-scale hydrogen storage technology. Liquid organic hydrogen carriers (LOHCs) improve the storage and handling of hydrogen by covalently bonding hydrogen to liquid organic skeletons through catalytic exothermic hydrogenation and endothermic dehydrogenation reactions.
[0003] At present, a variety of effective catalysts have been developed for LOHC, such as Pd-based, Ru-based and Ni-based. Among them, because of the high activity and catalytic stability of precious metal catalysts, attempts have been made to use them on large LOHC fixed beds. The general operation method is to place a certain mass of catalyst in a reaction tank, and then pump the LOHC liquid into the reaction tank through a hydraulic pump for hydrogen addition and dehydrogenation reaction, and then pump it out of the reaction tank after the reaction is completed. In this process, in order to ensure the normal operation of the large LOHC fixed bed, that is, the catalyst cannot enter the liquid flow pipeline with the flow of LOHC liquid to cause pipeline blockage, it is usually necessary to set a filter screen at both ends of the reaction tank, and the hole diameter of the filter screen is about 1mm~1.5mm. This requires that the catalyst installed in the reaction tank not only needs to have a large specific surface area, but also should be a particle with a length, width and height greater than 1.5mm. At the same time, the catalyst is also required to have a large mechanical strength under high temperature and high pressure to resist the impact of liquid flow on the catalyst particles. The above reaction conditions put forward higher requirements on the catalyst molding technology, which inevitably increases the cost of catalyst particle molding.
[0004] However, taking the commonly used spherical particle catalyst as an example, only the catalytic active sites on the surface of the spherical particles are effective, while the catalytic sites buried deep inside the spherical particles have no catalytic effect because they have no chance to contact LOHC. This results in the larger the size of the spherical particles, the lower the volume ratio of the effective active sites to the catalyst. In recent years, many researchers have proposed to load the active components on three-dimensional macroporous carriers such as nickel foam and copper foam to reduce the cost of catalyst molding and increase the dispersion of the active components on the carrier. However, relying on the electrostatic adsorption or chemical force between the active components and the three-dimensional macroporous materials, the carrier has limited constraints on the active components. Once the active components are separated from the catalyst carrier during the dehydrogenation process, the catalyst will completely lose its activity. In addition, since most foam metals are flake metals with higher density, this will result in too low a dispersion of low-content precious metal active components per unit area. Summary of the invention
[0005] 1. Technical problems to be solved by the present invention:
[0006] The present invention aims to provide a method for preparing a foamed sheet catalyst for organic liquid hydrogen storage / dehydrogenation, so as to solve the problem that the number of active sites of hydrogenation and dehydrogenation catalysts currently used on a fixed bed is small and the catalytic activity is low.
[0007] 2. The technical solution created by the present invention:
[0008] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a foam sheet catalyst for organic liquid hydrogen storage / dehydrogenation, the preparation method comprising the following preparation steps: A compound containing Pd or Ru is dissolved in a solvent to form a Pd or Ru solution; a nano-carrier and a binder are then added and stirred to obtain a suspension; after the suspension is stirred into a colloidal state, a foam metal is impregnated therein, and then the impregnated foam metal is dried and placed in a reduction furnace; finally, it is reduced in an Ar / H2 or H2 atmosphere to obtain a foam sheet catalyst for hydrogen storage / dehydrogenation in organic liquids.
[0009] Preferably, the mass volume ratio of the Pd or Ru compound to the solvent of the present invention is greater than 3g:1000mL, and the Pd or Ru element in the compound containing Pd or Ru accounts for 0.3%~3% of the sum of the mass of the Pd or Ru element and the nanocarrier; the added amount of the binder is less than 10% of the sum of the mass of the compound containing Pd or Ru and the nanocarrier.
[0010] Preferably, the mass of the Pd and / or Ru element in the compound containing Pd and / or Ru of the present invention, the mixture of the nano-carrier and the binder on the foam metal carrier is 0.1 g / cm 2 ~0.5g / cm2 .
[0011] Preferably, the compound containing Pd or Ru in the present invention is selected from one of PdCl2, Pd(NO3)2·2H2O, palladium acetate, palladium acetylacetonate, RuCl3, ruthenium acetate or ruthenium acetylacetonate.
[0012] Preferably, the solvent of the present invention is selected from one of water, ethanol, acetone, tetrahydrofuran or N,N-dimethylformamide.
[0013] Preferably, the nanocarrier of the present invention is selected from one of Al2O3, TiO2, SiO2 or graphene; the particle size of the nanocarrier is 20~100nm.
[0014] Preferably, the binder of the present invention is selected from one of PVP, sodium carboxymethyl cellulose or sodium alginate.
[0015] Preferably, the amount of the binder added in the present invention accounts for ≤10% of the mass fraction of the carrier.
[0016] Preferably, the foam metal of the present invention is selected from one of foam nickel, foam copper or foam aluminum.
[0017] Preferably, the reduction temperature of the present invention is 200° C. to 400° C., and the reduction time is 1 to 6 hours.
[0018] 3. Effects and advantages of the invention:
[0019] Compared with the prior art, the present invention has the following advantages: 1) The preparation method of the foam sheet catalyst for hydrogen storage / desorption in organic liquid of the present invention loads the catalyst in a foamy three-dimensional macroporous material with a certain mechanical strength, so that sufficient active sites are exposed in the organic liquid, thereby improving the catalytic activity of the catalyst; at the same time, the foam sheet catalyst for hydrogen storage / desorption in organic liquid of the present invention better solves the problem of uneven distribution caused by too low a loading amount of Pd or Ru on the foam metal.
[0020] 2) In the method for preparing the foamed sheet catalyst for organic liquid hydrogen storage / dehydrogenation of the present invention, the foamed nickel, foamed copper and foamed aluminum used are all mature commercial materials, which greatly reduces the cost of the catalyst.
[0021] 3) In the preparation method of the foamed sheet catalyst for organic liquid hydrogen storage / dehydrogenation of the present invention, the PVP, sodium carboxymethyl cellulose and alginate binder used have their own characteristics, which ensure the catalytic stability of the catalyst in LOHC. First, PVP has good chemical and physical structure stability at a reduction temperature of 200-400°C, and has good thermal stability at a reduction temperature of 200-400°C, which can ensure that the catalyst is firmly attached to the nickel foam, copper foam or aluminum foam. The carbonization temperature of sodium carboxymethyl cellulose is about 250°C, and it can be carbonized on the nickel foam, copper foam or aluminum foam during the reduction process. Under the action of the interatomic force, the carbonized carbon can firmly fix Pd or Ru on the nickel foam, copper foam or aluminum foam. The binder sodium alginate has good thermal stability under the condition that the reduction temperature is less than 300°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a physical picture of the unimpregnated nickel foam in Example 1 of the present invention.
[0023] Figure 2 This is a physical picture of the nickel foam, i.e., S1 catalyst, after impregnation in Example 1 of the present invention.
[0024] Figure 3 This is a SEM image of the organic liquid hydrogen storage / dehydrogenation foam sheet catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with embodiments and comparative examples. Example 1
[0026] Take 0.515 g of PdCl2 and dissolve it in 20 mL of water. After PdCl2 is completely dissolved, a solution is formed. Pour 10 g of Al2O3 with a diameter of 20 nm into the solution and stir evenly. Then add 1 g of sodium carboxymethyl cellulose and stir to obtain a suspension. After the suspension is stirred to a colloidal state (i.e., Pd / Al2O3 colloid), add 1 cm*5 cm*0.5 cm of nickel foam (such as Figure 1 As shown in the figure, the nickel foam was immersed in the colloid, and the nickel foam was taken out after 5 minutes and dried in an oven. Then the nickel foam was transferred to a reduction furnace and reduced at 400°C for 6 hours under an Ar / H2 atmosphere. After the reduction was completed, the catalyst was taken out to obtain the S1 catalyst (as shown in the figure). Figure 2 As shown in Figure 2), Pd accounts for 3% of the total mass of Pd / Al2O3, and the loading amount of Pd / Al2O3 on nickel foam is 0.1 g / cm 2 Its SEM morphology is as follows Figure 3As shown in the figure, since gas overflows from sodium carboxymethyl cellulose during the pyrolysis and carbonization process, this will leave some holes on the surface of the nickel foam. The existence of these holes increases the active sites of the S1 catalyst exposed in LOHC. The additional exposed active sites have a positive effect on the hydrogenation and dehydrogenation performance of the S1 catalyst.
[0027] 10 g of S1 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150 °C. Under the catalysis of S1 catalyst, the hydrogenation conversion rate of N-ethylcarbazole within 2 h was close to the theoretical value, which was 5.7%, and the 12H-NEC selectivity was >99%, as shown in Table 1.
[0028] The hydrogenated organic liquid and S1 catalyst were put back into the reactor and a continuous hydrogenation test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 6.2 L, and the conversion rate was >99% (calculated based on the theoretical hydrogenation amount of N-ethylcarbazole being 5.7%, the theoretical value of hydrogenation amount of 10 g N-ethylcarbazole is 6.2 L). As shown in Table 2.
[0029] Example 2 Take 0.253 g of Pd(NO3)2·2H2O and dissolve it in 20 mL of ethanol. After Pd(NO3)2 is completely dissolved, a solution is formed. Pour 10 g of TiO2 with a diameter of 50 nm into it and stir evenly. Then add 0.1 g of sodium alginate and stir to obtain a suspension. After the suspension is stirred to a colloidal state, 1 cm*5 cm*0.5 cm of foamed copper is immersed in the colloid. After 5 minutes, take out the foamed copper and dry it in an oven. Then transfer the foamed copper to a reduction furnace and reduce it at 300°C for 3 hours under a H2 atmosphere. After the reduction is completed, take out the catalyst to obtain the S2 catalyst, in which Pd accounts for 1% of the total mass of Pd / TiO2, and the loading amount of Pd / TiO2 on the foamed copper is 0.3 g / cm 2 .
[0030] 10 g of S2 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150 °C. Under the catalysis of S2 catalyst, the hydrogenation conversion rate of N-ethylcarbazole within 2 h was close to the theoretical value, which was 5.7%, and the 12H-NEC selectivity was >99%. As shown in Table 1. The excellent catalytic performance of S2 catalyst comes from the bonding force of sodium alginate that firmly binds the catalyst to the nickel foam, so that the active sites of S2 catalyst exposed in LOHC in the entire hydrogenation and dehydrogenation process play a stable catalytic role.
[0031] The hydrogenated organic liquid and S2 catalyst were put back into the reactor and a continuous hydrogenation test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 6.2 L, and the conversion rate was >99% (calculated based on the theoretical hydrogenation amount of N-ethylcarbazole being 5.7%, the theoretical value of hydrogenation amount of 10 g N-ethylcarbazole is 6.2 L). As shown in Table 2. Example 3
[0032] Take 0.106 g of palladium acetate and dissolve it in 20 mL of acetone. After the palladium acetate is completely dissolved, a solution is formed; 10 g of SiO2 with a diameter of 100 nm is poured into it and stirred evenly; then 0.3 g of PVP is added and stirred to obtain a suspension. After the suspension is stirred to a colloidal state, 1 cm*5 cm*0.5 cm of foamed aluminum is immersed in the colloid. After 5 minutes, the foamed aluminum is taken out and placed in an oven to dry. Then the foamed aluminum is transferred to a reduction furnace and reduced at 250°C for 2 hours under a H2 atmosphere. After the reduction is completed, the catalyst is taken out to obtain the S3 catalyst, in which Pd accounts for 0.5% of the total mass of Pd / SiO2, and the loading amount of Pd / SiO2 on the foamed aluminum is 0.5 g / cm 2 .
[0033] 10 g of S3 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150 °C. Under the catalysis of S1 catalyst, the hydrogenation conversion rate of N-ethylcarbazole within 2 h was close to the theoretical value, which was 5.7%, and the 12H-NEC selectivity was >99%. As shown in Table 1.
[0034] The hydrogenated organic liquid and S3 catalyst were put back into the reactor and a continuous hydrogenation test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 6.2 L, and the conversion rate was >99% (calculated based on the theoretical hydrogenation amount of N-ethylcarbazole being 5.7%, the theoretical value of hydrogenation amount of 10 g N-ethylcarbazole is 6.2 L). As shown in Table 2. Example 4
[0035] Take 0.086 g of acetylacetonate palladium and dissolve it in 20 mL of tetrahydrofuran. After the acetylacetonate palladium is completely dissolved, a solution is formed; 10 g of 20 nm graphene (RGO) is poured into it and stirred evenly, and then 0.5 g of PVP is added to obtain a suspension. After the suspension is stirred to a colloidal state, 1 cm*5 cm*0.5 cm of nickel foam is immersed in the colloid. After 5 minutes, the nickel foam is taken out and placed in an oven to dry. Then the nickel foam is transferred to a reduction furnace and reduced at 200 ° C for 1 hour under a H2 atmosphere. After the reduction is completed, the catalyst is taken out to obtain the S4 catalyst, in which Pd accounts for 0.5% of the total mass of Pd / RGO, and the loading amount of Pd / RGO on the nickel foam is 0.5 g / cm2 .
[0036] 10 g of S4 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150°C. Under the catalysis of S4 catalyst, the hydrogenation conversion rate of N-ethylcarbazole within 2 h was close to the theoretical value, which was 5.7%, and the 12H-NEC selectivity was >99%, as shown in Table 1.
[0037] The hydrogenated organic liquid and S4 catalyst were put back into the reactor and a continuous hydrogenation test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 6.2 L, and the conversion rate was >99% (calculated based on the theoretical hydrogenation amount of N-ethylcarbazole being 5.7%, the theoretical value of hydrogenation amount of 10 g N-ethylcarbazole is 6.2 L). As shown in Table 2. Example 5
[0038] Take 0.634 g of RuCl3 and dissolve it in 20 mL of tetrahydrofuran. After RuCl3 is completely dissolved, a solution is formed. Pour 10 g of Al2O3 with a diameter of 20 nm into it and stir evenly. Then add 1 g of sodium carboxymethyl cellulose and stir to obtain a suspension. After the suspension is stirred to a colloidal state, immerse 1 cm*5 cm*0.5 cm of nickel foam into the colloid. After 5 minutes, take out the nickel foam and dry it in an oven. Then transfer the nickel foam to a reduction furnace and reduce it at 400 ° C for 3 hours under an Ar / H2 atmosphere. After the reduction is completed, take out the catalyst to obtain the S5 catalyst, in which Ru accounts for 3% of the total mass of Pd / Al2O3, and the loading amount of Ru / Al2O3 on the nickel foam is 0.3 g / cm 2 .
[0039] 10 g of S5 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150°C. Under the catalysis of S5 catalyst, the hydrogenation conversion rate of N-ethylcarbazole within 2 h was close to the theoretical value, which was 5.7%, and the 12H-NEC selectivity was >99%, as shown in Table 1.
[0040] The hydrogenated organic liquid and S5 catalyst were put back into the reactor and a continuous hydrogenation test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 6.2 L, and the conversion rate was >99% (calculated based on the theoretical hydrogenation amount of N-ethylcarbazole being 5.7%, the theoretical value of hydrogenation amount of 10 g N-ethylcarbazole is 6.2 L). As shown in Table 2. Example 6
[0041] Take 0.851 g of ruthenium acetate and dissolve it in 20 mL of tetrahydrofuran. After the ruthenium acetate is completely dissolved, a solution is formed; 10 g of Al2O3 with a diameter of 20 nm is poured into it and stirred evenly, and then 0.5 g of sodium carboxymethyl cellulose is added and stirred to obtain a suspension. After the suspension is stirred to a colloidal state, 1 cm*5 cm*0.5 cm of nickel foam is immersed in the colloid. After 5 minutes, the nickel foam is taken out and placed in an oven to dry. Then the nickel foam is transferred to a reduction furnace and reduced at 400 ° C for 3 hours under an Ar / H2 atmosphere. After the reduction is completed, the catalyst is taken out to obtain the S6 catalyst, in which Ru accounts for 3% of the total mass of Ru / Al2O3, and the loading amount of Ru / Al2O3 on the nickel foam is 0.1 g / cm 2 .
[0042] 10 g of S6 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150°C. Under the catalysis of S6 catalyst, the hydrogenation conversion rate of N-ethylcarbazole within 2 h was close to the theoretical value, which was 5.7%, and the 12H-NEC selectivity was >99%, as shown in Table 1.
[0043] The hydrogenated organic liquid and S6 catalyst were put back into the reactor and a continuous hydrogenation test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 6.2 L, and the conversion rate was >99% (calculated based on the theoretical hydrogenation amount of N-ethylcarbazole being 5.7%, the theoretical value of hydrogenation amount of 10 g N-ethylcarbazole is 6.2 L). As shown in Table 2. Example 7
[0044] Take 1.219 g of ruthenium acetylacetonate and dissolve it in 20 mL of tetrahydrofuran. After the ruthenium acetylacetonate is completely dissolved, a solution is formed; 10 g of Al2O3 with a diameter of 20 nm is poured into it and stirred evenly; then 0.5 g of PVP is added and stirred to obtain a suspension. After the suspension is stirred to a colloidal state, 1 cm*5 cm*0.5 cm of nickel foam is immersed in the colloid. After 5 minutes, the nickel foam is taken out and placed in an oven to dry. Then the nickel foam is transferred to a reduction furnace and reduced at 200°C for 2 hours under an Ar / H2 atmosphere. After the reduction is completed, the catalyst is taken out to obtain the S7 catalyst, in which Ru accounts for 3% of the total mass of Ru / Al2O3, and the loading amount of Ru / Al2O3 on the nickel foam is 0.1 g / cm 2 .
[0045] 10 g of S7 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150°C. Under the catalysis of S7 catalyst, the hydrogenation conversion rate of N-ethylcarbazole within 2 h was close to the theoretical value, which was 5.7%, and the 12H-NEC selectivity was >99%, as shown in Table 1.
[0046] The hydrogenated organic liquid and S7 catalyst were put back into the reactor and a continuous hydrogenation test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 6.2 L, and the conversion rate was >99% (calculated based on the theoretical hydrogenation amount of N-ethylcarbazole being 5.7%, the theoretical value of hydrogenation amount of 10 g N-ethylcarbazole is 6.2 L). As shown in Table 2.
[0047] Comparative Example 1
[0048] Take 0.515 g of PdCl2 and dissolve it in 20 mL of water. After PdCl2 is completely dissolved, a solution is formed; 10 g of Al2O3 with a diameter of 1.5 mm is poured into it and stirred evenly. Then the impregnated catalyst precursor is placed in an oven to dry, and then the dried catalyst precursor is transferred to a reduction furnace and reduced at 400°C for 6 hours under an Ar / H2 atmosphere. After the reduction is completed, the catalyst is taken out to obtain J1 catalyst with a Pd loading of 3%.
[0049] 10 g of J1 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150 °C. Under the catalysis of J1 catalyst, the hydrogenation conversion rate of N-ethylcarbazole was 4.7% within 2 h, and the selectivity of 12H-NEC was about 75%, as shown in Table 1.
[0050] The hydrogenated organic liquid and J1 catalyst were put back into the reactor and a continuous hydrogen release test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was 4.5 L, and the conversion rate was 73%, as shown in Table 2.
[0051] Compared with S1 to S7 catalysts, J1 catalyst exhibits lower catalytic activity. The main reason for this phenomenon is that the Pd content in J1 catalyst is relatively high. Although a high content of Pd can provide higher catalytic activity in the early stage of catalytic hydrogenation reaction, since this reaction is an exothermic process, the initial reaction is too intense, which will generate a large amount of heat, causing Pd particles to aggregate and undergo secondary growth. However, since the binding between Pd and Al2O3 mainly depends on electrostatic adsorption, this force is relatively weak. Therefore, when the morphology of J1 catalyst changes significantly, Pd particles easily fall off the Al2O3 carrier, resulting in loss of activity. In contrast, S1 to S7 catalysts are restricted by the pore structure and binder of the foam metal, which can effectively inhibit the growth of Pd particles caused by strong heat release, thereby avoiding the activity loss problem faced by J1 catalyst.
[0052] Comparative Example 2
[0053] The Pd / Al2O3 catalyst was prepared by the method of Example 1, except that no binder was added in Comparative Example 2. 0.515 g of PdCl2 was taken and dissolved in 20 mL of water. After PdCl2 was completely dissolved, a solution was formed; 10 g of Al2O3 with a diameter of 20 nm was poured into it and stirred evenly, and a 1 cm*5 cm*0.5 cm nickel foam was immersed in the colloid. After 5 minutes, the nickel foam was taken out and dried in an oven. The nickel foam was then transferred to a reduction furnace and reduced at 400°C for 6 hours under an Ar / H2 atmosphere. After the reduction was completed, the catalyst was taken out to obtain the J2 catalyst. Through ICP testing, it was found that Pd accounted for 3% of the total mass of Pd / Al2O3, and the loading amount of Pd / Al2O3 on the nickel foam was 0.08 g / cm 2 Although the amount of Pd in the J2 catalyst is consistent with that in the J1 catalyst, there is a lack of a binder between the active components in the J2 catalyst and the nickel foam, and the catalyst is simply loaded on the nickel foam by electrostatic adsorption, so a large amount of Pd / Al2O3 components will be lost.
[0054] 10 g of J2 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150 °C. Under the catalysis of J2 catalyst, the hydrogenation conversion of N-ethylcarbazole within 2 h was 3.5%, and the selectivity of 12H-NEC was about 57%, as shown in Table 1.
[0055] The hydrogenated organic liquid and J2 catalyst were put back into the reactor and a continuous hydrogen release test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 2 L, and the conversion rate was 32%, as shown in Table 2.
[0056] The poor catalytic performance of J2 catalyst is due to the lack of bonding between the catalytic active material and the nickel foam, and the catalyst active components are easily separated from the foam metal, resulting in a catalyst deactivation phenomenon similar to that of J1 catalyst. In addition, since the Pd content in J2 catalyst is lower than that in J1 catalyst, the overall activity of J2 catalyst is worse than that of J1 catalyst.
[0057] Comparative Example 3
[0058] The Pd / Al2O3 catalyst was prepared by the method of Example 1, except that an excess amount of binder was added in Comparative Example 3. Take 0.515 g of PdCl2 and dissolve it in 20 mL of water. After PdCl2 is completely dissolved, a solution is formed; 10 g of Al2O3 with a diameter of 20 nm is poured into it and stirred evenly, and then 1.5 g of sodium carboxymethyl cellulose is added and stirred to obtain a suspension. After the suspension is stirred to a colloidal state, 1 cm*5 cm*0.5 cm of nickel foam is immersed in the colloid. After 5 minutes, the nickel foam is taken out and placed in an oven to dry. The nickel foam is then transferred to a reduction furnace and reduced at 400°C for 6 hours under an Ar / H2 atmosphere. After the reduction is completed, the catalyst is taken out to obtain a J3 catalyst, in which Pd accounts for 3% of the total mass of Pd / Al2O3, and the loading amount of Pd / Al2O3 on the nickel foam is 0.5 g / cm 2 10 g of J3 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor, and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150 °C. Under the catalysis of J3 catalyst, the hydrogenation conversion rate of N-ethylcarbazole was 3.3% within 2 h, and the selectivity of 12H-NEC was about 55%, as shown in Table 1.
[0059] The hydrogenated organic liquid and J3 catalyst were put back into the reactor and a continuous hydrogen release test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was 3.2 L and the conversion rate was 51%, as shown in Table 2.
[0060] The poor catalytic activity of the J3 catalyst is due to the fact that the addition of a large amount of binder causes the precursor to have poor heat and mass transfer during the reduction process, resulting in thermal decomposition of the precursor surface due to temperature influence, while the decomposition temperature cannot be reached inside the precursor. The active sites of the catalyst are tightly wrapped by the binder and cannot play a catalytic role.
[0061] Comparative Example 4
[0062] The Pd / Al2O3 catalyst was prepared by the method of Example 1, except that the nickel foam was replaced with a block-shaped melamine formaldehyde resin in Comparative Example 4. 0.515 g of PdCl2 was taken and dissolved in 20 mL of water. After PdCl2 was completely dissolved, a solution was formed. 10 g of Al2O3 with a diameter of 20 nm was poured into the solution and stirred evenly. Then 1 g of sodium carboxymethyl cellulose was added and stirred to obtain a suspension. After the suspension was stirred to a colloidal state, a 1 cm*5 cm*0.5 mm block-shaped melamine formaldehyde resin was immersed in the colloid. After 5 minutes, the melamine formaldehyde resin was taken out and dried in an oven. Then the melamine formaldehyde resin was transferred to a reduction furnace and reduced at 400 °C for 6 h in an Ar / H2 atmosphere. After the reduction was completed, the catalyst was taken out to obtain catalyst J4, in which Pd accounted for 3% of the total mass of Pd / Al2O3 and the loading amount of Pd / Al2O3 on the melamine formaldehyde resin was 0.5 g / cm 2 It is worth noting that, because the melamine formaldehyde resin will break the resin molecules at high temperature, resulting in changes in the molecular structure, at the same time, the block-shaped melamine formaldehyde resin will also be pulverized, making the final J4 catalyst powdery.
[0063] 10 g of J4 catalyst and 10 g of N-ethylcarbazole were placed in a high-pressure reactor and N-ethylcarbazole was continuously hydrogenated at 4 MPa and 150 °C. Under the catalysis of J4 catalyst, the hydrogenation conversion of N-ethylcarbazole within 2 h was 4.7%, and the 12H-NEC selectivity was about 76%, as shown in Table 1.
[0064] The hydrogenated organic liquid and J4 catalyst were put back into the reactor and a continuous hydrogen release test was performed at 180°C. After 2 h of reaction, the amount of hydrogen released was close to 4.4 L, and the conversion rate was 71%, as shown in Table 2.
[0065] The poor catalytic activity of J4 catalyst is because the structure of melamine formaldehyde resin has been destroyed during the high-temperature reduction process, and carbonization has occurred during the reduction process, which reduces its mechanical strength and makes its stability as a N-ethylcarbazole dehydrogenation catalyst gradually deteriorate as the dehydrogenation process proceeds.
[0066] Table 1 is a table of hydrogenation data of the catalysts of Examples 1 to 7 and Comparative Examples 1 to 4.
[0067]
[0068] Table 2 is a table of hydrogen release data of the catalysts of Examples 1 to 7 and Comparative Examples 1 to 4.
[0069]
[0070] In addition, during the preparation of the catalyst, if the reduction temperature exceeds 400°C, the mechanical strength of the foam metal will be weakened, and the binder will also be over-carbonized. The combined effect of these two conditions will lead to a significant decrease in the overall mechanical strength of the catalyst.
Claims
1. A method for preparing a foamed sheet catalyst for hydrogen storage / dehydrogenation in an organic liquid, characterized in that: The method comprises the following preparation steps: A compound containing Pd or Ru is dissolved in a solvent to form a Pd or Ru solution; a nano-carrier and a binder are then added and stirred to obtain a suspension; after the suspension is stirred into a colloidal state, a foam metal is impregnated therein, and then the impregnated foam metal is dried and placed in a reduction furnace; finally, it is reduced in an Ar / H2 or H2 atmosphere to obtain a foam sheet catalyst for hydrogen storage / dehydrogenation in organic liquids.
2. The method according to claim 1, characterized in that: The mass volume ratio of the Pd or Ru compound to the solvent is greater than 3g:1000mL, the Pd or Ru element in the Pd or Ru-containing compound accounts for 0.3% to 3% of the sum of the mass of the Pd or Ru element and the nanocarrier; the added amount of the binder is less than 10% of the sum of the mass of the Pd or Ru-containing compound and the nanocarrier.
3. The method according to claim 1, characterized in that: The loading amount of the mixture of the mass of Pd and / or Ru elements in the compound containing Pd and / or Ru, the nano-carrier and the binder on the foam metal carrier is 0.1 g / cm 2 ~0.5g / cm 2 .
4. The method according to claim 1 or 2, characterized in that: The compound containing Pd or Ru is selected from one of PdCl2, Pd(NO3)2·2H2O, palladium acetate, palladium acetylacetonate, RuCl3, ruthenium acetate or ruthenium acetylacetonate.
5. The method according to claim 1 or 2, characterized in that: The solvent is selected from one of water, ethanol, acetone, tetrahydrofuran or N,N-dimethylformamide.
6. The method according to claim 1 or 2, characterized in that: The nanocarrier is selected from one of Al2O3, TiO2, SiO2 or graphene; the particle size of the nanocarrier is 20-100nm.
7. The method according to claim 1 or 2, characterized in that: The binder is selected from one of PVP, sodium carboxymethyl cellulose or sodium alginate.
8. The method according to claim 7, characterized in that: The added amount of the binder accounts for ≤10% of the mass fraction of the carrier.
9. The method according to claim 1 or 2, characterized in that: The foam metal is selected from one of foam nickel, foam copper or foam aluminum.
10. The method according to claim 1, characterized in that: The reduction temperature is 200°C to 400°C and the reduction time is 1 to 6 hours.